DCTPP1, an Oncogene Regulated by miR-378a-3p, Promotes Proliferation of Breast Cancer via DNA Repair Signaling Pathway - Niu, Ming; Shan, Ming; Liu, Yang; Song, Yanni; Han, Ji-guang; Sun, Shanshan; Liang, Xiao-shuan; Zhang, Guo-qiang (Frontiers in Oncology, 2021)
Breast cancer (BC) constitute one of the most lethal cancers worldwide, especially in women and its dismal survival could be due to a high proliferation rate. Human all-alpha dCTP pyrophosphatase 1 (DCTPP1) is implicated in numerous diseases, including cancers. However, its role in BC is unclear. Here, we used bioinformatic analyses on ONCOMINE, UALCAN, and GEPIA to determine DCTPP1 expression in BC. We find that elevated DCTPP1 levels correlate with poor BC prognosis. DCTPP1 silencing inhibited BC cell proliferation in vitro, as well as in vivo. Our data show that this tumorigenic effect depends on DNA repair signaling. Moreover, we found that DCTPP1 is directly modulated by miR-378a-3p, whose downregulation is linked to BC progression. Here, we identified miR-378a-3p is down-regulate in BC. Up-regulate miR-378a-3p can inhibit BC cell growth and inhibit proliferation. This study shows that reduced miR-378a-3p level enhance DCTPP1 expression in BC, which promotes proliferation by activating DNA repair signaling in BC.